High-risk endometrial cancer may be benefit from adjuvant radiotherapy plus chemotherapy - Miao, Jin-Wei; Deng, Xiao-Hong (Chinese Journal of Cancer Research; Vol 24, No 4 (December 07, 2012): Chinese Journal of Cancer Research, 2012)
Objective: To present patterns of practice and outcomes in the adjuvant treatment of intermediate- and high-risk endometrial cancer. Methods: Retrospective data on 224 women with intermediate-risk and high-risk endometrial cancer from 1999 to 2006 were reviewed. All patients underwent surgical staging. Patterns of adjuvant treatment, consisting of pelvic radiotherapy, chemotherapy, and radiotherapy plus chemotherapy, were assessed. The 3- and 5-year disease-specific survival (DSS) rates were calculated using the Kaplan-Meier method. Results: The difference in 5-year DSS rate was statistically significant between adjuvant group and non-adjuvant group (80.65% vs. 63.80%, P=0.040). In 110 high-risk patients who underwent adjuvant treatment, both 5-year DSS rate and recurrent rate were significantly different in combined radiotherapy and chemotherapy group compared with radiotherapy alone and chemotherapy alone groups (DSS rate, P=0.049; recurrent rate, P=0.047). In 83 intermediate-risk women who underwent adjuvant treatment, there was no significant difference in 5-year DSS rate and recurrence rate among the combined radiotherapy and chemotherapy, radiotherapy alone and chemotherapy alone groups (DSS rate, P=0.776; recurrent rate, P=0.937). Conclusions: Adjuvant radiotherapy plus chemotherapy is associated with a higher 5-year DSS rate and lower recurrence rate compared with radiotherapy alone and chemotherapy alone in high-risk endometrial cancer patients. Patients with intermediate-risk endometrial cancer may be not likely to benefit from adjuvant combined radiotherapy and chemotherapy.